A survey of mixed Begomovirus infection in solanaceae and fabaceae at different altitudes in East Java, Indonesia. (25th February 2019) - Lukman, Rudy; Afifuddin, Ahmad; Van Deynze, Allen; Hill, Theresa; Jimenez, Randi
Abstract: A multiplex primer set was developed to detect four Begomoviruses in East Java, Indonesia, i.e. Tomato leaf curl New Delhi virus (ToLCNDV), Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), Pepper yellow leaf curl Indonesia virus (PepYLCIV) and Mungbean yellow mosaic India virus (MYMIV). Survey at different altitudes found that begomoviruses infecting pepper, tomato and long bean were more variable, while in eggplant and string bean were more uniform. As a single virus, TYLCKaV infected eggplant, and sometimes tomato and pepper; PepYLCIV infected pepper, tomato and long bean; ToLCNDV only infected long bean and tomato at low frequency; and MYMIV infected beans. Mixed infection occurred more frequently in the low altitude areas. Subsequent examination indicated that Cucumber mosaic virus (CMV) and potyviruses were also responsible for diseased fabaceous. Our data suggest a relationship between altitudes and virus species occurrence. However, which viral species infects a crop is mainly influenced by the crop rather than by altitude.